2015
DOI: 10.1039/c5ra19893c
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer MoS2 quantum dots as catalysts for efficient hydrogen evolution

Abstract: A multi-exfoliation route was used to prepare monolayer MoS2 quantum dots with improved electrocatalytic activity for hydrogen evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 43 publications
5
36
0
Order By: Relevance
“…These numbers are in good agreement with reported values for 1L MoS 2 by Voiry et al [65], but high compared to other reports in literature with TOFs of about 10-100 s −1 [4,69]. Overall, the TOF increases for more negative overpotentials as expected, and the determined TOF at 0 V is in the range of about 1 s −1 , again in good agreement with literature values for thin MoS 2 layers [68].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These numbers are in good agreement with reported values for 1L MoS 2 by Voiry et al [65], but high compared to other reports in literature with TOFs of about 10-100 s −1 [4,69]. Overall, the TOF increases for more negative overpotentials as expected, and the determined TOF at 0 V is in the range of about 1 s −1 , again in good agreement with literature values for thin MoS 2 layers [68].…”
Section: Discussionsupporting
confidence: 82%
“…At 0.3 V, the TOFs reach approximately 4 · 10 3 s −1 , 1 · 10 4 s −1 , and 2 · 10 4 s −1 for bulk, 2L and 1L MoS 2 -flakes, respectively. These values are in excellent agreement with the reported values for monolayer MoS 2 by Voiry et al [65], but rather high compared to other reports in literature with deduced TOFs of about 10-100 s −1 [4,69].…”
Section: Electrochemical Characterization Without Illuminationsupporting
confidence: 82%
“…The peak spacing for MoS 2 QDs (22.5 cm -1 ) was less than that of bulk MoS 2 (25.7 cm -1 ) revealing the monolayer structure of MoS 2 QDs. [37] It was also observed that, the intensity of A 1g mode decreases with increase in times of exfoliation due to the decrease in layer-layer interactions. [54] …”
Section: Properties Of Mos 2 Quantum Dots (Qds)mentioning
confidence: 99%
“…Also, Qiao et al [37] have reported the monolayer MoS 2 QDs with enhanced HER catalytic activity having lower onset over potential of about 120 mV and a small Tafel slope of 69 mV dec -1 . Various catalysts such as, MoS 2 nanosheets (NSs), MoS 2 nanoflowers (NFs), MoS 2 QD with their composites MoS 2 NSs/RGO, MoS 2 NFs/RGO and MoS 2 QD/RGO were synthesized by the facile sonication method.…”
Section: Electrocatalytic Activity In Hermentioning
confidence: 99%
See 1 more Smart Citation